HUMAN RESOURCE COMPETENCY AND BUDGETING PARTICIPATION IN PREDICTING THE ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT - Hernita, Nita; Sri Silvia Pamuji, Rita; Riyadi, Wulan; Wida Rahmayani, Melia; Achmad Mahiri, Eli; Risdayanti; Afifah, Asmi (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
With only IDR 17,012,500, or 10.50% of the predetermined target of IDR 162,053,250, Cigasong Sub-district, Majalengka Regency, West Java, Indonesia, achieved the lowest village fund management in Majalengka Regency in the first quarter of 2017. The consolidated report on the realization of the absorption of the first phase of village funding for Cigasong District was delayed as a result. Thus, it suggests that there is still a lack of accountability in Cigasong District's village budget management. The purpose of this research is to ascertain how budgeting involvement and human resource competency affect the accountability of village fund management in Cigasong District. This study's focus is on village administrators that oversee village finances in every hamlet inside Cigasong Sub-district. This study is quantitative in nature and uses primary data collected through questionnaires using Likert scale measurement. Using a sample of fifty village officials, the saturation sampling technique was used. Utilizing SPSS version 21, data analysis is performed via descriptive analysis, hypothesis testing, multiple linear regression analysis, classical assumption testing, and coefficient of determination analysis. According to the study, budgeting participation has a considerable impact on village finance management accountability, whereas human resource competency has no discernible impact on the same.